Effect Of Dapagliflozin On Lipid Profile In Type-2 Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2023)
Objective: Aim was to determine the effects of Dapagliflozin on lipid profile in patients of Type-2 Diabetes Mellitus.Study Design: Randomized placebo-controlled trialPlace and Duration:Methods: This randomized placebo-controlled trial was carried out at Combined Military Hospital, Peshawar from 1st February 2022 to 30th April 2022 on type-2 diabetes patients having dyslipidemia. Baseline blood samples for serum LDL-C, HDL-C and triglycerides were collected after a 12- hour fast. Patients were randomized to receive either Dapagliflozin 10 mg OD or placebo on top of their existing regular antidiabetic and lipid lowering medications. Lipid profile was rechecked after 12 weeks. Changes in Lipid Profile from baseline was the primary outcome. Secondary outcomes were changes in HBA1c, Fasting Blood Sugar, body weight and blood pressure.Results: Patients mean age was 55.9 ±12.39 years and had mean BMI 29.7 ±10.88 kg/m2. There were 17 (65.4%) males and 9 (34.6%) were females. 10 (38.5%) patients were educated and 19 (73.1%) cases were from rural areas. 11 (42.3%) patients had smoking history. HTN, IHD and obesity were the most common comorbidities among all cases. LDL-C was significantly lower in the Dapagliflozin group compared to the placebo group from 4.6±3.16 to 1.9±1.7 mmol/l , with a p value of 0.002 for each. We also found reduction in triglycerides in group I from 3.2±1.4 to 2.1±1.11 mmol/l while increased in HDL-C was noted 2.1±1.8 to 3.7 ±2.5 mmol/l. With a p value of 0.005, the levels of HbA1c, fasting plasma glucose (FPG), and systolic blood pressure (SBP) were significantly lower after 12 weeks.Conclusion: We found that patients with T2DM experienced significant lipid lowering effects from Dapagliflozin as compared to placebo. Significant reduction in LDL-C, Triglycerides, Systolic BP, Fasting Plasma Glucose, HbA1c and increased HDL-C were also noted in Dapagliflozin group.